An Influence Perceived Organizational Support on Affective Commitments with Satisfaction Work as a Mediation Variable - Suryo Sudikno; Feby Milanie; Cahyo Pramono (CERED Indonesia Institute, 2022)
The purpose ofthis study was to determine how the role of job satisfaction mediating the effect of perceived organizational support on organizational commitment. This research was conducted at PT. Aerofood ACS Deli Serdang. The number of samples taken were 89 employees, using the proportionate random sampling technique. Data collection was obtained from the results of interviews, observation and questionnaires. Data analysis using classical assumption test, path analysis, sobel test. Based on the results of the analysis, was found that perceived organizational support had a positive and significant effect on job satisfaction. Perceived organizational support has a positive and significant effect on organizational commitment. Job satisfaction has a positive and significant effect on organizational commitment. Perceived organizational support has a positive and significant effect on organizational commitment through mediating job satisfaction. Efforts to increase employees' sense of organizational commitment, organizations should be able to provide support to their employees because the higher the support given to employees, the higher the job satisfaction felt by employees.